TEOLOGI KERUKUNAN: BUYA SYAKUR DAN GAGASAN PENANGGULANGAN RADIKALISME BERAGAMA - Muhammad Ihza Fazrian (Academic Journal of Islamic Principles and Philosophy, 2024)
Religious radicalism is a serious problem because it can trigger conflicts between believers. This problem comes from certain religious groups that claim their beliefs are the most correct, such as radical Muslims. Negative behaviors such as the phenomena of blaming others, violence, and even terrorism, occur due to religious radicalism. This research discusses the thoughts of a Muslim scholar named Buya Syakur about the theology of harmony as an effort to overcome religious radicalism. This type of research is a document research with descriptive-analytical method. The primary sources are two videos of Buya Syakur's lectures, Moderasi Beragama Merajut Nasionalisme & Toleransi Beragama and Dialog Kerukunan Islam–Buddha, as well as two of his works entitled Merawat Pluralitas and Berbagi Kebahagiaan: Mengenal Maqom-Maqom Tasawuf. The research findings showed that the concept of theology of harmony perspective of Buya Syakur is divided into three aspects, reviewing the concept of kafir and taqwa, looking critically through the life history of the Prophet Muhammad, and the importance of maintaining plurality and cooperation between religious communities.